Inhibition of Human Neutrophil Extracellular Trap (NET) Production by Propofol and Lipid Emulsion - Meier, Angela; Chien, Jason; Hobohm, Laura; Patras, Kathryn Ann; Nizet, Victor; Corriden, Ross (Frontiers in Pharmacology, 2019)
Uncontrolled bacteremia is a common and life threatening condition that can lead to sepsis and septic shock with significant morbidity and mortality. Neutrophil granulocytes, the most abundant phagocytic leukocyte of the innate immune system, play an essential role in capturing and killing invading pathogens. Their antimicrobial repertoire includes the formation of Neutrophil Extracellular Traps (NETs), chromatin-based, web-like structures of DNA that facilitate the capture and killing of bacteria. In sepsis, however, it has been suggested that the uncontrolled release of NETs worsens disseminated coagulation and promotes venous thrombosis. Here, we describe how clinically relevant concentrations of the commonly used sedative propofol as well as a lipid composition similar to the propofol carrier impair NET production by human neutrophils. Drugs commonly administered in the Intensive Care Unit (ICU) may impact the inflammatory response to either worsen or improve clinical outcomes and may therefore be considered for additional therapeutic effects if clinical studies confirm such findings.